Kulwap”: a trend of health promotion during the COVID-19 pandemic, Implementation of the STIKES Buleleng Community Partnership Project - Ni Kadek Diah Purnamayanti; Kadek Yudi Aryawan; Made Sundayana (Journal of Community Empowerment for Health, 2022)
The pandemic of COVID-19 has brought the global community into a new perspective of living. Due to the social distancing protocol, face to face meetings should be avoided. This could be a barrier in implementing the previous health promotion programs which were based on group gatherings. Hence, nowadays, the online approach has become a promising strategy. The intensive use of social media platforms in Indonesia serves as a great opportunity to penetrate the public awareness of society. The initiation of “Kulwap” (Kuliah WhatsApp or lecturing by WhatsApp), which is an approach to gather a group of people in a WhatsApp Group and deliver a lecture to this group through the application is also being implemented in STIKes Buleleng Bali. The aim of this study was to assess the effectiveness of WhatsApp as a media of health promotion. It is a part of the community partnership integrated into the educational process of nursing students. During the program, there were four major topics promoted: Non-Communicable Disease (NCD), Communicable Disease, and Wellness and Child Health Issues. This program succeeded in involving 357 participants who lived in Bali. Based on the participants’ feedback, the engagement was successful due to the use of WhatsApp as the preferred social media platform (84.3%), the beneficial contents being shared during the Kulwap (65.5%), the attractiveness of media being used in the lecture (82.8%) and the way of delivery was easy to be understood (70.3%). Almost all (98.6%) of the participants expressed their willingness to rejoin the program. Therefore, the study concluded that the use of Kulwap serves is an effective and acceptable strategy to establish a health promotion initiative during the current COVID-19 pandemic.